2011
DOI: 10.5851/kosfa.2011.31.1.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soybean Sauce and Pre-rigor Muscle on Physicochemical Properties of Frozen Hanwoo Patties

Abstract: In this study, we evaluated the physicochemical and sensorial properties of frozen Hanwoo beef patties prepared from prerigor and post-rigor muscle with soybean sauce or sodium chloride. The pH of the soybean sauce treatments was lower than the sodium chloride treatments (p<0.05); however, the Hanwoo patty prepared from pre-rigor muscle with soybean sauce had a lower cooking loss and smaller diameter than the Hanwoo patty prepared under the same conditions from post-rigor muscle (p<0.05). The addition of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…Jeon et al (2002) reported that the low pH value of the soybean sauce is caused by the proliferation of lactic acid bacteria during the fermentation period, which might be the reason for a low pH value of meats treated with soybean sauce (T1, T2, and T3). A similar result was reported by Kim et al (2011) where the pH value of frozen Hanwoo patties containing soybean sauce was lower than the pH value of those made with sodium chloride for both pre-and postrigor Hanwoo muscle.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Jeon et al (2002) reported that the low pH value of the soybean sauce is caused by the proliferation of lactic acid bacteria during the fermentation period, which might be the reason for a low pH value of meats treated with soybean sauce (T1, T2, and T3). A similar result was reported by Kim et al (2011) where the pH value of frozen Hanwoo patties containing soybean sauce was lower than the pH value of those made with sodium chloride for both pre-and postrigor Hanwoo muscle.…”
Section: Resultssupporting
confidence: 87%
“…The TS and T3 treatments had the highest values for all textural properties (p<0.05), and they were not significant (p>0.05). Similar result was obtained by Kim et al (2011). In the case of soybean sauce treatments (T1, T2, and T3), the hardness was higher as the salt concentration in soybean sauce increased 0.5% to 2.0% (p<0.05).…”
supporting
confidence: 83%
See 2 more Smart Citations
“…It contains approximately 15–20% salt, 50–70% water, free sugars, isoflavones, peptides, and organic acids that are produced from the soybeans during the fermentation process (Jeon et al, 2002 ; Shim et al, 2008 ). The sauce has a characteristic black color due to the presence of melanoidins, which are formed when carbonyl compounds and amino compounds combine together (Kim et al, 2011 ). The melanoidins present in soybean sauce are responsible for its antioxidant potential (Choi et al, 1990 ).…”
Section: Fermented Food Of Koreamentioning
confidence: 99%